The product of the given expression (x − 3)^2 would be equal to x^2 - 6x + 9.
Suppose that we've a function y = f(x) such that f(x) is quadratic.
When y = 0, then the values of x for which f(x) = 0 is called solution of quadratic equation f(x) = 0
This solution gives values of x, and when we plot x and f(x), we'd see that the graph intersects the x-axis at its solution points.
Example: For x² + 5x + 6 = 0, the solutions are x = -3, and x = -2.
The graph of y = x² + 5x + 6 will intersect the x-axis at x= -3 and x=-2 (and those are the only intersection it will do on x-axis).
The given expression is
Learn more about solutions of a quadratic equation here:
#SPJ2
Answer:
x2 − 6x + 9
Step-by-step explanation:
Took a test and got it right
x + y - 2 = 0
x - y - 2 = 0
the answer seems to be x+y-2=0
-14 = 4a
Answer:
a = -3 1/2
Step-by-step explanation:
To solve the equation for a, divide each side by 4.
-14 = 4a
-14/4 = 4a/4
-14/4 = a
Simplify the fraction by dividing the top and bottom by 2.
-7/2 =a
This is an improper fraction, so change to a mixed number.
2 goes into 7 3 times with 1 left over.
-7/2 = -3 1/2
a = -3 1/2
-14=4a
=
a=
x + y
x - y
B) -
x - y
-x + y
C) -
x - y
-x - y
D) -
x + y
-x + y
Answer:
Step-by-step explanation:
1 - 3s - s + 8 -2 = 1 + 8 - 2 -3s - s
= 9 - 2 - 4s
= 7 - 4s
Here, 1 , 8 & (-2) are like term and when we add we get 7
-3s & -s are like terms. Add the coefficient of s , -3 +(-1) = -4
Answer:
y 5 horas entre mediterráneo que pasa por Perú